Nilai-Nilai Pendidikan Islam Yang Terdapat Pada Pulut Kuning Dalam Acara Khataman Al-Qur’an Di Desa Teluk Lancar Kecamatan Bantan Kabupaten Bengkalis - Yusin, Muhammad; Prayuzka, Mildo; Robi’ah, Robi’ah (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
The goal to be achieved in this study is to find out the values of Islamic education contained in pulut kuning in the khataman al-Qur'an event in Teluk Smooth Village, Bantan District, Bengkalis Regency. The method used in this research is to use a descriptive method. The subjects of this study were the people of Teluk Lancar village who had knowledge of pulut kuning. Data collection was carried out by conducting  interviews, documentation and literature study. The results showed that the implementation of the khataman al-qur'an with yellow pulut was often carried out in the village of Teluk Lancar, Bantan District, Bengkalis Regency. The results of the study of khatman al-Qur'an using yellow pulut include preparation, core and cover. The process of preparing for the Khataman al-Qur'an includes preparing the time for execution, preparation for the venue, and preparation for the host. Then the main event includes a prayer of congratulations, sungkeman, and so on. The final result of this research is that pulut kuning in the ceremony of circumcision of the Koran is only symbolic and is not required because in the khatman of the Koran during the holy month of Ramadan, pulut kuning is not used. Pulut kuning is just a hereditary tradition, if it is not made it will feels incomplete